2022
DOI: 10.1038/s41419-022-04564-8
|View full text |Cite
|
Sign up to set email alerts
|

PTBP3 modulates P53 expression and promotes colorectal cancer cell proliferation by maintaining UBE4A mRNA stability

Abstract: The RNA binding protein PTBP3 was recently reported to play a critical role in multiple cancers, and the molecular mechanisms involved RNA splicing, 3′ end processing and translation. However, the role of PTBP3 in colorectal cancer (CRC) remains poorly explored. Herein, PTBP3 was upregulated in CRC and associated with a poor prognosis. PTBP3 knockdown in colorectal cancer cell lines restricted CRC proliferative capacities in vitro and in vivo. Mechanistically, PTBP3 regulated the expression of the E3 ubiquitin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Ptbp3 encodes a protein that is critical in RNA splicing and transcriptional regulation ( Xie et al, 2022 ). The PTBP3 protein mediates TGF-β-induced epithelial-to-mesenchymal transition ( Dong et al, 2022 ) and can serve as an immunomodulatory biomarker of cancer ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ptbp3 encodes a protein that is critical in RNA splicing and transcriptional regulation ( Xie et al, 2022 ). The PTBP3 protein mediates TGF-β-induced epithelial-to-mesenchymal transition ( Dong et al, 2022 ) and can serve as an immunomodulatory biomarker of cancer ( Chen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, immunosuppression mediated by interactions between PD-1 on Tregs and PD-L1 on CD8 + T cells has been investigated and was attenuated by PD-1 inhibition [36]. T helper 17 (Th17) cells, another effector CD4 + T cell subset, play a controversial role in tumor immunity and their levels have been correlated with both unfavorable and favorable outcomes [37]. For example, Th17 cells were reported to signi cantly enhance breast cancer progression by secreting cytokines, including IL-22, IL-21, and IL-6 [38], while a clinical trial showed that CTLA4 inhibitors can induce Th17 cells in patients with melanoma and that levels of IL-17 detected in ascites can predict patient's survival [39].…”
Section: Discussionmentioning
confidence: 99%
“…Several variations in UBE4A, including loss of function, have been implicated in neuroblastoma tumors, neurodevelopment impairment, 95,230 and several cancers including prostate 231 and colorectal cancer. 232 As in the case of E2 enzyme family, E4 factors have not been extensively studied and tested in mammalian models. Recent UBE4A deletion models were generated in insects and C. elegans.…”
Section: E4 Chain Ubiquitin Elongation Factorsmentioning
confidence: 99%